(untitled) (Research, Society and Development, 2022)
Introduction: health practices in Brazil have changed over the years, adopting a more preventive approach. Thus, linked to primary care, the Family Health Strategy (ESF) emerged, responsible for health promotion in Brazilian families, including the provision of dental care. However, there are difficulties in accessing these services, due to the lack of supplies and the unavailability of some dental treatments by the SUS, in addition to insufficient coverage of the population by the oral health teams (ESB). Therefore, the study aims to describe the evolution of coverage of oral health teams in the Northeast region from 2018 to 2021. Methodology: an ecological study was carried out, analyzing the nine northeastern states, seeking secondary data on the e-gestor platform (Ministry of Health), with a time frame from 2018 to 2021. The absolute and relative frequencies of coverage of the ESBs linked to the ESF of each state were collected and organized, calculating the arithmetic mean of the percentages and arranged in graphs in the Excel software for representative purposes. Results: there was a progressive increase in the coverage of ESBs since 2018 in the Northeastern states. Of these, Piauí has the highest coverage, while Bahia has the lowest one, although it has shown growth in this rate over the years. Sergipe was the only state to register a drop. Conclusion: despite different rates, the Northeast region has the highest coverage of oral health teams per population, but a more effective distribution is needed, in addition to an increase in the supply of services and improved access to oral health..